O Livro 4 de Afonso III - Diana Fontão (Medievalista)
The trajectory of the manuscript with the shelf mark Livro 4 de Inquirições de Afonso III (Book of Inquiries 4 of Afonso III) has particularities, both at an archival level and in terms of its content, which make it stand out among the Portuguese Books of Inquiries. This article seeks to identify its journey in the Torre do Tombo Nacional Archive, looking at its inventories and its inclusion in the series to which it currently belongs. Its contents are also analyzed, in particular the documentation whose copy motivated the production of the codex: documentation relating to Portuguese Muslim communities in the 15th century. The aim is also to clarify whether this manuscript can be considered a Book of Inquiries. To this end, a brief analysis was made of the subject matter of the General Inquiries and how it was added to the codex format it currently presents.